Potato not Pope: human brain potentials to gender expectation and agreement in Spanish spoken sentences - Wicha, Nicole Y.Y. (2003)
Event-related potentials were used to examine the role of grammatical gender in auditory sentence comprehension. Native Spanish speakers listened to sentence pairs in which a drawing depicting a noun was either congruent or incongruent with sentence meaning, and agreed or disagreed in gender with the immediately preceding spoken article. Semantically incongruent drawings elicited an N400 regardless of gender agreement. A similar negativity to prior articles of gender opposite to that of the contextually expected noun suggests that listeners predict specific words during comprehension. Gender disagreements at the drawing also elicited an increased negativity with a later onset and distribution distinct from the canonical N400, indicating that comprehenders attend to gender agreement, even when one of the words is only implicitly represented by a drawing.